Accessibility and availability: A cross-cultural study of shopper responses to online retail stock-outs - Gruen, Thomas; Corsten, Daniel (Taylor & Francis, 2021)
Accessibility of products in online retail is an expected part of the shopper experience journey. Frequent products are not accessible due to non-availability. Introduced by Sheth and Sisodia, the 4A’s framework articulates how success in any marketing program depends on four dimensions: Awareness, Acceptability, Affordability, and Accessibility. This article demonstrates how, like dominos fall, marketing investments can fail when the final 4A’s stage, Accessibility, is not adequately addressed in online retailing. Surveying more than 2,000 shoppers across five European and Asian countries that encountered a non-available item while shopping online for one of six fast-moving consumer goods categories, the research study examines shoppers’ switching behavior when Accessibility has been interrupted in the purchasing stage of the customer journey. The overall goal is to better understand how shoppers change their behavior, and it examines a variety of causes that drive switching behavior, whether it be to switch stores, switch brands, or switch intentions when the item they desired is unavailable. Switching behavior was found to vary greatly among the five countries, but less between categories, and switching was greatly affected by the way shoppers encountered the non-available item. The study concludes with recommendations to address Accessibility both in product availability and shoppers’ transaction costs.
Keywords: Shopper behavior;Out-of-stock;Online retail;Availability;Stock-out; Shopper behavior; Out-of-stock; Online retail; Availability; Stock-out